I1 Global spread of stec and managing the consequences. (12th March 2018) - Smith-Palmer, A; Hawkins, G; Couper, S; Maxwell, H; Reynolds, B; Harkins, V; Allison, L; Hanson, M
Abstract : Shiga toxin-producing E. coli (STEC) was first recognised as a food-borne pathogen in 1982, when it was isolated during two outbreaks of haemorrhagic colitis associated with undercooked burgers in the United States. Since then, STEC has become established as an important global gastrointestinal pathogen. STEC can colonise the gastrointestinal tract of wild, farmed, and domesticated animals and be shed in their faeces. Cattle are considered the most important reservoir for STEC in humans; infection in cattle is non-pathogenic. Transmission to humans can occur as a result of direct contact with STEC-contaminated faecal material, from handling or petting animals or by exposure to faecally contaminated soil or vegetation during recreational or occupational activities. Exposure can also occur from consumption of contaminated food or water or via person to person transmission. Reports of STEC infection in Scotland increased markedly in the mid 1990's and rates remain high when compared to other UK and European countries. In 2016 the overall rate of STEC in Scotland was 4.6 per 100, 000, with the highest incidence in individuals aged under 16 years. In comparison, the 2015 rate for the UK was 2.05 per 1 00 000 and for the EU was 1.27 per 1 00 000. Serotype O157 continues to be the most frequently identified serotype in Scotland accounting for 75% of culture confirmed cases in 2016. The number of non-O157 infections has increased steadily in recent years, partially explained by changes in diagnostic practices. Among the non-O157 isolates, STEC O26 was the most common accounting for 19% in 2016. Clinical presentation ranges from asymptomatic infection to mild non-bloody diarrhoea, through bloody diarrhoea and haemorrhagic colitis to haemolytic uraemic syndrome (HUS), thrombotic microangiopathy and, in a small number of cases, death. HUS develops in approximately 10%–15% of E. coli O157 cases, with the highest rates in those under 15 years or over 65 years of age, HUS mortality is reported to be between 3% and 5%. Among the 2016 STEC cases in Scotland with enhanced surveillance information, 35% required hospitalisation.